Livistona chinensis: Chinese Fan Palm: ENH-524/ST365, rev. 4/2014 - Broschat, Timothy K. (EDIS, 2014)
The Chinese fan palm is relatively slow growing, typically reaching about 30 feet in height. Its fan-shaped, costapalmate leaves can be 3 to 4 feet across and up to 6 feet long. Petioles of juvenile palms are spiny, but have few or no spines in adult palms. Because of its gracefully drooping leaf segment tips, this species is sometimes called the “fountain palm”. Young specimens are slow to form a trunk, which has led to the unfortunate practice of planting these palms close together as a ground cover. Eventually, most of those closely planted palms will have to be removed to accommodate their 10 to 12 foot spread. This revised 3-page fact sheet was written by Timothy K. Broschat, and published by the UF Department of Environmental Horticulture, April 2014. ENH-524/ST365: Livistona chinensis: Chinese Fan Palm (ufl.edu)